Preparation method and application of self-supporting B-doped NiFe LDHs oxygen evolution electrode

By vertically growing B-doped NiFe LDHs on a foam nickel substrate using a one-step impregnation method to form a self-supported oxygen evolution electrode with a porous "nanosphere" structure, the problem of low catalytic activity and stability of the oxygen evolution electrode in the prior art is solved, and efficient catalytic oxygen evolution reaction under alkaline conditions is achieved.

CN119530868APending Publication Date: 2025-02-28YULIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411741435.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The catalytic activity and stability of the oxygen evolution electrode used in the prior art under alkaline conditions are not high, resulting in low efficiency in electrolyzing hydrogen production, and large-scale application is hindered by the slow oxygen evolution reaction of the anode.

Method used

B-doped NiFe LDHs are grown vertically on the foam nickel substrate by one-step impregnation method to form a porous "nanoflower ball" structure self-supported oxygen evolution electrode, avoiding the blockage of active sites caused by the use of binders.

Benefits of technology

It realizes efficient catalytic oxygen evolution reaction under alkaline conditions, reduces the overpotential, improves the stability and catalytic activity of the electrode, and makes the hydrogen production process more efficient in water electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005162681780000011
    Figure HDA0005162681780000011
  • Figure HDA0005162681780000012
    Figure HDA0005162681780000012
  • Figure HDA0005162681780000021
    Figure HDA0005162681780000021
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a self-supporting B-doped NiFe LDHs oxygen evolution electrode, and belongs to the field of hydrogen production by alkaline electrolysis of water. According to the electrode, foamed nickel serves as a substrate, the substrate is loaded with B-doped NiFe LDHs serving as a catalytic active component, the morphology of the B-doped NiFe LDHs is that a plurality of porous nanometer flower ball structures which are formed by arranging and stacking nanosheets in a staggered mode grow on the foamed nickel substrate, and the diameter of each nanometer flower ball is 500 nm to 2 microns. According to the preparation method, the B-doped NiFe LDHs OER electrode directly and vertically grown on the foamed nickel substrate is obtained through a simple one-step impregnation method, the morphology of a synthetic catalyst can be effectively controlled under a mild condition, and the B-doped NiFe LDHs OER electrode has good catalytic activity and stability. The invention can be applied to renewable fuel cells, photoelectrocatalysis, alkaline anion exchange membrane electrolyzed water, seawater electrolysis and electrolytic hydrogen generator devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a self-supporting B-doped NiFe LDHs oxygen evolution electrode, and belongs to the field of hydrogen production by alkaline water electrolysis. Background Art

[0002] Hydrogen production by water electrolysis has the advantages of high catalytic efficiency, high purity of hydrogen production, and environmental friendliness, and is regarded as one of the most promising hydrogen production technologies. Hydrogen production by alkaline water electrolyzers has attracted widespread attention because it can use low-cost non-precious metal electrocatalysts to replace precious metals Ir and Ru, although its energy conversion efficiency (≈70%) needs further improvement. However, the large-scale application of water electrolysis is mainly hindered by the slow oxygen evolution reaction at the anode. Therefore, it is necessary to design and explore oxygen evolution electrodes with high catalytic activity and long life.

[0003] The core of the electrolysis process is the electrocatalyst required for the electrochemical reaction, which directly affects the electrolysis efficiency, electrolysis energy consumption, electrolysis cost and the life of the electrolytic cell. Recently, there has been a trend of increasing research on non-precious metal oxygen evolution catalysts used under alkaline conditions.

[0004] Patent CN106149025A describes a one-step electrosynthesis method for nickel-iron hydrotalcite nanosheets. Although the method is simple and fast, there is no relevant data showing that the electrode prepared by this method can obtain excellent OER performance, and the micromorphology of the electrode prepared by this method is difficult to control. Patent CN115044939A describes a self-supporting nickel-based double metal hydroxide oxygen evolution electrode prepared by a one-step impregnation method, but the OER activity and stability of the obtained electrode are still not high.

[0005] Recent studies have found that the introduction of electron-deficient B into NiFe LDHs can effectively promote the valence state transition of Ni (from Ni 2+ Formation of Ni 3+ ), which is beneficial to improve OER activity. For example, the literature (Nat Commun, 2022, 13: 6094-6103) found that adding electron-deficient B to NiFe LDHs is an effective method for preparing efficient OER electrodes; this is because the addition of B can reduce Ni 2+ Oxidized to Ni 3+The required overpotential also reduces the starting potential of OER and enhances OER kinetics. The literature (Appl Catal B: Environ, 2022, 317-427: 121713-121723) synthesized an amorphous NiFeB alloy OER powder catalyst by surface self-reconstruction. In addition, the literature (J Alloys Compd, 2022, 903: 163741-163747) prepared an amorphous NiFeB alloy OER powder catalyst by a two-step method of sodium borohydride (NaHBO3) reduction and low-temperature annealing. However, the above studies obtained powder catalysts, which require the use of binders in practical applications, which will block some active sites and cause the OER catalytic performance to decrease. In contrast, these problems can be effectively avoided if a self-supporting electrode is used. However, there are few studies on the preparation of self-supporting NiFeB hydroxides for OER electrodes. The paper (Appl Catal B: Environ, 2022, 317-427: 121713-121723) reported the synthesis of NiFeB hydroxide OER electrode on nickel foam substrate by electrodeposition. Although this study effectively avoided the use of binder, the electrode prepared by electrodeposition was unevenly distributed on the nickel foam substrate and it was difficult to scale up the electrode, which was not conducive to the needs of industrial production. Summary of the invention

[0006] The purpose of the present invention is to provide a B-doped NiFe LDHs oxygen evolution electrode for use under alkaline conditions and a preparation method thereof, and the electrode is used as an anode of AEMWE under conditions close to alkaline industrial water electrolysis, ensuring that the electrode prepared according to the method can enable the water electrolysis reaction to be carried out efficiently under a smaller applied voltage.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] The invention provides a self-supporting B-doped NiFe LDHs oxygen evolution electrode, wherein the electrode comprises a substrate and a catalytically active component, wherein the substrate is nickel foam, and the active component is B-doped NiFe LDHs. The morphology of the active component B-doped NiFe LDHs is that it grows vertically on the surface of the nickel foam substrate and is composed of many nanosheets, and the nanosheets are staggered and stacked to form a porous "nano flower ball" structure, and the diameter of each "nano flower ball" is between 500nm and 2μm.

[0009] In the above technical solution, further, the thickness of the nanosheet is 40 to 120 nm; the multiple "nano flower balls" are densely distributed on the nickel foam substrate; the thickness of the B-doped NiFe LDHs catalytic layer is 5 to 10 μm; preferably, the thickness of the nanosheet is 40 to 70 nm.

[0010] In the above technical solution, further, the electrode grows vertically on the surface of the nickel foam, the thickness of the nickel foam is 0.8-1 mm, and Ni>99.90%.

[0011] In the above technical solution, further, the B content in the B-doped NiFe LDHs is 9-38wt%; the Ni content in the B-doped NiFe LDHs is 70-75wt%; the Fe content in the B-doped NiFe LDHs is 7-9wt%; the catalytic active component loading per unit area on the nickel foam substrate is 0.045-0.055g cm -2 .

[0012] In the above technical scheme, further, the present invention uses a simple one-step impregnation method to obtain an oxygen evolution electrode composed of many thin nanosheets vertically grown on the surface of a nickel foam substrate under relatively mild conditions, and the nanosheets are staggered and stacked to form a porous "nano flower ball" structure. The preparation method includes the following steps:

[0013] (1) Preparation of precursor solution: Weigh nickel inorganic salt, iron inorganic salt and boron inorganic salt in sequence, dissolve them in deionized water, and stir until a uniform light green precursor solution is obtained;

[0014] (2) One-step impregnation method: The above-mentioned precursor solution is transferred to a watch glass, and the cleaned nickel foam is immersed in the watch glass, so that the precursor solution completely immerses the nickel foam substrate. After the impregnation reaction is carried out at room temperature (25-30°C) for a certain period of time, a brown-yellow B-doped NiFe LDHs electrode vertically grown on the nickel foam substrate is obtained and washed; the obtained brown-yellow electrode is transferred to a vacuum drying oven for drying, and finally a self-supporting B-doped NiFe LDHs oxygen evolution electrode is obtained.

[0015] In the above technical solution, further, in the precursor solution of step (1), the molar concentration of the nickel inorganic salt is 0.05 to 0.1 mol L -1 , containing iron inorganic salt molar concentration of 0.005~0.01mol L -1 ; The molar concentration of boron inorganic salt is 0.05~0.2mol L -1 Preferably, the molar concentration of the boron inorganic salt is 0.08 to 0.17 mol L -1 ;;The molar ratio of nickel organic salt, iron organic salt and boron organic salt is 1:0.1:0.5~2.

[0016] In the above technical scheme, further, the immersion conditions of step (2) should be controlled to be room temperature immersion, specifically immersion at 25-30°C for 1-7 days; the drying conditions are vacuum drying, the drying temperature is 50-100°C, and the drying time is 12-24h.

[0017] In the above technical solution, further, the nickel foam substrate of step (2) needs to be pre-treated, and the pre-treatment conditions are: 3 mol L -1 The hydrochloric acid, deionized water and ethanol are ultrasonically washed for 5 to 10 minutes and dried; the drying is vacuum drying, the drying temperature is 50 to 100° C., and the drying time is 12 to 24 hours.

[0018] Furthermore, in the above technical solution, the washing condition in step (2) is to wash with deionized water until the pH value reaches 7.

[0019] Furthermore, in the above technical solution, the time for stirring in step (1) to obtain the light green precursor solution is not less than 30 minutes.

[0020] Furthermore, in the above technical solution, the B-doped NiFe LDHs oxygen evolution electrode synthesized by one-step impregnation can be used to catalyze the oxygen evolution reaction in the process of electrolyzing water to produce hydrogen under alkaline conditions. It can be applied to the process of alkaline water electrolysis or seawater electrolysis in renewable fuel cells, photoelectrocatalysis, water electrolysis cells, alkaline water electrolysis hydrogen generators.

[0021] The self-supporting electrode prepared by the method has good oxygen evolution electrocatalytic performance and stability under alkaline conditions.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. Compared with the commonly used synthesis method, the preparation method of the present application does not require any surfactant, precipitant and high-temperature treatment method. Only a simple one-step impregnation method can be used to synthesize B-doped NiFe LDHs oxygen evolution electrode at room temperature and normal pressure, which can realize large-scale preparation and facilitate industrial production.

[0024] 2. Adding electron-deficient B to NiFe LDHs is an effective method for preparing efficient OER electrodes; this is because the addition of B can reduce the Ni 2+ Oxidized to Ni 3+ The required overpotential also reduces the onset potential of OER and enhances the OER kinetics, giving it good catalytic activity and stability.

[0025] 3. Compared with powdered catalysts, the self-supporting B-doped NiFe LDHs oxygen evolution electrode prepared by the method of the present invention has higher oxygen evolution catalytic activity, and the overpotential required for hydrogen production by water electrolysis is smaller; the morphology is controllable; and compared with carbon-supported oxygen evolution electrocatalysts, it has better stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is the SEM image of the self-supporting B-doped NiFe LDHs oxygen evolution electrode synthesized and prepared in Example 1.

[0027] Figure 2 The self-supporting B-doped NiFe LDHs oxygen evolution electrode obtained in the steps of Example 1 was used to test the oxygen evolution performance at 25°C using a three-electrode system. -1 The polarization curve was obtained by linear voltammetry scanning using KOH solution as the electrolyte.

[0028] Figure 3 The self-supporting B-doped NiFe LDHs oxygen evolution electrode obtained in the steps of Example 1 was used at 25°C using a three-electrode system with 1 mol L -1 The test curve of stability performance test is carried out with KOH solution as electrolyte.

[0029] Figure 4 The self-supporting NiFe LDHs oxygen evolution electrode obtained in the steps of Example 1 was electrolyzed at 70°C and 1 mol L -1 KOH solution was used as the electrolyte, and the obtained electrode was used as the anode of AEMWE to perform an IV curve test.

[0030] Figure 5 This is a SEM image of the self-supporting nickel-iron double metal hydroxide oxygen evolution electrode obtained by the steps described in Example 2.

[0031] Figure 6 The self-supporting nickel-iron double metal hydroxide oxygen evolution electrode obtained in the steps of Example 2 was used at 25°C and a three-electrode system was used with 1 mol L -1 The polarization curve was obtained by linear voltammetry scanning using KOH solution as the electrolyte.

[0032] Figure 7 The self-supporting B-doped NiFe (0.05 mol L -1 ) SEM image of oxygen evolution electrode.

[0033] Figure 8 The self-supporting B-doped NiFe (0.05 mol L -1 ) Oxygen evolution electrode, polarization curve obtained by linear voltammetric scanning curve of OER test in a three-electrode system with 1 M KOH as electrolyte at 25°C.

[0034] Fig. 9 The self-supporting B-doped NiFe (0.20 mol L -1 ) SEM image of oxygen evolution electrode.

[0035] Fig.10 The self-supporting B-doped NiFe (0.20 mol L -1 ) Oxygen evolution electrode, polarization curve obtained by linear voltammetric scanning curve of OER test in a three-electrode system with 1 M KOH as electrolyte at 25°C. DETAILED DESCRIPTION

[0036] The preparation method, characteristics and applications of the self-supporting B-doped NiFe LDHs oxygen evolution electrode are further described below in conjunction with the accompanying drawings, but the present invention is not limited in any way.

[0037] Example 1

[0038] The preparation method (one-step impregnation method) is as follows:

[0039] At room temperature, weigh 2.38 g (0.10 mol L -1 ) of NiCl2·6H2O, 0.28g (0.01mol L -1 ) of FeSO4·7H2O and 0.62 g (0.10 mol L -1 ) was dissolved in 100 mL of deionized water and stirred for 30 min to obtain a uniform precursor solution; the cleaned foam nickel substrate (the foam nickel substrate has a thickness of 1 mm, Ni≥99.9wt%, and is manufactured by Taiyuan Lizhiyuan Battery Co., Ltd.) was immersed in the precursor solution at room temperature (25-30°C) for 7 days, then taken out and rinsed with a large amount of deionized water, and vacuum dried at 60°C for 12 h to obtain a self-supporting B-doped NiFe hydroxide oxygen evolution electrode.

[0040] Depend on Figure 1 It can be seen that after the impregnation reaction, at room temperature and pressure, the synthesized self-supporting B-doped NiFe hydroxide oxygen evolution electrode grows vertically on the nickel foam substrate, and is composed of many nanosheets, which are staggered and stacked to form a porous "nano flower ball" structure. The diameter of each "nano flower ball" is 500nm to 2μm, the thickness of the nanosheet is about 40 to 60nm, and each "nano flower ball" is densely distributed on the nickel foam substrate. The thickness of the B-doped NiFe LDHs catalyst layer is 5 to 10μm.

[0041] Three-electrode test: At room temperature (25°C), a three-electrode system was used to pass oxygen to a saturated concentration of 1 mol L -1 KOH solution was used as the electrolyte to perform LSV scanning on the self-supporting B-doped NiFe hydroxide oxygen evolution electrode, such as Figure 2 The electrode prepared by this method has a -1 100 mA cm in KOH electrolyte solution-2 At a current density of 100 mA cm, the overpotential is 270 mV (not corrected for iR). -2 It can run stably and continuously for 1008h at a current density of Figure 3 )

[0042] AEMWE test: The loading is 0.4 mg cm -2 70wt.% Pt / C is coated on the alkaline anion membrane as the cathode of AEMWE, and the anode is the oxygen evolution electrode prepared in Example 1. The cathode and anode are separated by an alkaline membrane and hot pressed to form a membrane electrode. Finally, the membrane electrode, flow field and end plate are assembled into an AEMWE electrolytic cell. The effective area of ​​the membrane electrode is 2×2cm 2 , the test temperature is 70℃.

[0043] The self-supporting B-doped NiFe LDHs hydroxide oxygen evolution electrode prepared in Example 1 was used as the anode of AEMWE. The polarization curve is shown in Figure 4 As shown, under the following conditions close to industrial alkaline electrolysis water (70°C, 1 mol L -1 KOH electrolyte), the single cell performance is 0.5A cm -2 When the electrolysis voltage is 1.61 V, the experimental results show that the electrode has a good prospect for industrial application.

[0044] Example 2

[0045] As described in Example 1, at room temperature, weigh 2.38 g (0.10 mol L -1 ) of NiCl2·6H2O, 0.28g (0.01mol L -1 ) was dissolved in 100 mL of deionized water and stirred for 30 min to obtain a uniform light green precursor solution. The cleaned nickel foam was immersed in the light green solution for 7 days, and then the obtained electrode was rinsed with deionized water until the pH was 7 and then placed at 60 ° C for 12 h in vacuum drying. Finally, a NiFe LDHs oxygen evolution electrode (such as Figure 5 ).

[0046] Three-electrode test: At room temperature (25°C), a three-electrode system was used to pass oxygen to a saturated concentration of 1 mol L -1 The KOH solution was used as the electrolyte and the self-supporting electrode was subjected to LSV scanning. Figure 6 The electrode prepared by the method of Example 2 has a -1 100mAcm in KOH electrolyte solution -2 At a current density of , the overpotential is 324mV (not corrected for iR). Figure 5 It can be seen that the NiFe LDHs without B doping grow vertically in the shape of "thorn balls" on the surface of the nickel foam substrate and are evenly distributed.

[0047] Comparative Example 1

[0048] As described in Example 1, at room temperature, weigh 2.38 g (0.10 mol L -1 ) of NiCl2·6H2O, 0.28g (0.01mol L -1 ) of FeSO4·7H2O and 0.31 g (0.05 mol L -1 ) was dissolved in 100 mL of deionized water and stirred for 30 min to obtain a uniform precursor solution; the cleaned nickel foam substrate (the nickel foam substrate had a thickness of 1 mm, Ni ≥ 99.9 wt %, and was manufactured by Taiyuan Lizhiyuan Battery Co., Ltd.) was immersed in the precursor solution, and after immersion for 7 days at room temperature (25-30° C.), it was taken out and rinsed with a large amount of deionized water, and vacuum dried at 60° C. for 12 h to obtain a self-supporting B-doped NiFe (0.05 mol L -1 ) oxygen evolution electrode (such as Figure 7 ). It can be seen from the figure that when B doped NiFe (0.05 mol L -1 ) concentration is low, only part of the B-doped NiFe (0.05 mol L -1 ) hydroxide is generated (the figure shows that there is a blank part on the nickel foam substrate).

[0049] Three-electrode test: At room temperature (25°C), a three-electrode system was used to pass oxygen to a saturated concentration of 1 mol L -1 The KOH solution was used as the electrolyte and the electrode was scanned by LSV. Figure 8 The self-supporting electrode prepared by this method is -1 In KOH solution, 100 mA cm -2 At a current density of 1.5 mol / L, the overpotential is 330 mV (without iR correction). This performance is lower than that of the self-supporting B-doped NiFe LDHs hydroxide oxygen evolution electrode obtained in Example 1. This is because the concentration of B in the current solution is 0.05 mol L -1 When B-doped NiFe LDHs (0.05 mol L -1 ) are unevenly distributed and sparse on the nickel foam substrate, and some areas are blank (see Figure 7 ), which may be caused by the small amount of B added, which greatly reduces the exposure of active sites and catalytic efficiency.

[0050] Comparative Example 2

[0051] According to the steps described in Example 1, at room temperature, weigh 2.38 g (0.10 mol L -1 ) of NiCl2·6H2O, 0.28g (0.01mol L -1 ) of FeSO4·7H2O and 1.24 g (0.20 mol L -1 ) was dissolved in 100 mL of deionized water and stirred for 30 min to obtain a uniform precursor solution; the cleaned nickel foam substrate (the nickel foam substrate had a thickness of 1 mm, Ni ≥ 99.9 wt %, and was manufactured by Taiyuan Lizhiyuan Battery Co., Ltd.) was immersed in the precursor solution, and after immersion for 7 days at room temperature (25-30° C.), it was taken out and rinsed with a large amount of deionized water, and vacuum dried at 60° C. for 12 h to obtain a self-supporting B-doped NiFe hydroxide oxygen evolution electrode (such as Fig. 9 ).

[0052] Three-electrode test: At room temperature (25°C), a three-electrode system was used to pass oxygen to a saturated concentration of 1 mol L -1 KOH solution was used as the electrolyte to perform LSV scanning on the self-supporting electrode, such as Fig.10 The self-supporting electrode prepared by this method has a -1 100 mA cm in KOH electrolyte solution -2 The potential at the electrolysis current density is 338mV. This performance is lower than that of the self-supporting B-doped NiFe hydroxide oxygen evolution electrode obtained in Example 1. This may be due to the fact that the nanosheet layer of the NiFeB hydroxide catalyst layer grown on the foam nickel substrate obtained after a larger amount of B addition is introduced into the NiFe LDHs is relatively thicker (75-120nm) than that of Example 1 (40-60nm). As a result, the B-doped NiFe hydroxide oxygen evolution electrode obtained in this example has a lower catalytic activity in the alkaline oxygen evolution reaction.

[0053] pass Figure 1 , Figure 5 , Figure 7 and Fig. 9 Analysis shows that the B-doped NiFe hydroxide oxygen evolution electrode prepared by the present application method grows vertically on the nickel foam substrate and is composed of many thin nanosheets (40-60 nm) and the nanosheets are staggered and stacked to form a porous "nano flower ball" ( Figure 1 ), high catalytic activity.

Claims

1. A self-supporting B-doped NiFe LDHs oxygen evolution electrode, characterized in that: The electrode is based on nickel foam, and the catalytic active component loaded on the substrate is B-doped NiFe LDHs. The morphology of the B-doped NiFe LDHs is that a plurality of nanosheets are stacked and arranged in an interlaced manner to form a porous "nano flower ball" structure grown on the nickel foam substrate, and the diameter of each "nano flower ball" is between 500nm and 2μm.

2. The electrode according to claim 1, characterized in that: The thickness of the nanosheet is 40 to 120 nm; the multiple "nano flower balls" are densely distributed on the nickel foam substrate; the thickness of the B-doped NiFe LDHs catalyst layer is 5 to 10 μm; preferably, the thickness of the nanosheet is 40 to 70 nm.

3. The electrode according to claim 1, characterized in that: The B content in the B-doped NiFe LDHs is 9-38wt%; the Ni content in the B-doped NiFe LDHs is 70-75wt%; the Fe content in the B-doped NiFe LDHs is 7-9wt%; the loading amount of the catalytic active component per unit area on the nickel foam substrate is 0.045-0.055g cm -2 .

4. A method for preparing the electrode according to any one of claims 1 to 3, characterized in that: The steps include: (1) Preparing a precursor solution: taking a nickel inorganic salt, an iron inorganic salt and a boron inorganic salt and stirring them with water to dissolve them to obtain a precursor solution; (2) Impregnation: completely immersing the nickel foam substrate into the precursor solution obtained in the above step (1) for 1 to 7 days at room temperature; washing and drying the obtained nickel foam substrate to obtain the self-supporting B-doped NiFe LDHs oxygen evolution electrode.

5. The preparation method according to claim 4, characterized in that: The precursor solution in step (1): the molar concentration of the nickel inorganic salt is 0.05 to 0.1 mol L -1 The molar concentration of inorganic iron salt is 0.005~0.01mol L -1 ; The molar concentration of boron inorganic salt is 0.05~0.2mol L -1 Preferably, the molar concentration of the boron inorganic salt is 0.08 to 0.17 mol L -1 ; The molar ratio of nickel inorganic salt to iron inorganic salt to boron inorganic salt is 1:0.1:0.5~2.

6. The preparation method according to claim 4, characterized in that: The nickel foam substrate in step (2) needs to be pre-treated. The pre-treatment conditions are: the nickel foam is treated with 3 mol L -1 Ultrasonic washing with hydrochloric acid, deionized water and ethanol for 5 to 10 minutes and drying; The drying is vacuum drying, the drying temperature is 50-100° C., and the drying time is 12-24 hours.

7. The preparation method according to claim 4, characterized in that: The hydrolysis reaction in step (2) is carried out by immersion at room temperature for 1 to 7 days; the drying is vacuum drying; The vacuum drying conditions are as follows: the drying temperature is 50-100°C and the vacuum drying time is 12-24h; The washing condition is to wash with deionized water in sequence until the pH is neutral.

8. The preparation method according to claim 4, characterized in that: The stirring time in step (1) is not less than 30 minutes.

9. The electrode according to any one of claims 1 to 3 is used to catalyze the oxygen evolution reaction in the process of producing hydrogen by electrolysis of water under alkaline conditions.

10. The electrode according to any one of claims 1 to 3 is used as an oxygen evolution catalyst in renewable fuel cells, photoelectrocatalysis, alkaline anion exchange membrane water electrolysis, seawater electrolysis and electrolytic hydrogen generator devices.

Citation Information

Patent Citations

  • One-step electro-synthesis method of iron-layered double hydroxide nanosheet array

    CN106149025A

  • Preparation method and application of self-supporting nickel-based double-metal hydroxide oxygen evolution electrode

    CN115044939A